Spillover Effects of Old-Age Pension across Generations: Family Labor Supply and Child Outcomes - Katja Maria Kaufmann; Yasemin Özdemir; Han Ye (Institute of Labor Economics (IZA), 2022)
We study the impact of grandparental retirement decisions on family members' labor supply and child outcomes by exploiting a Dutch pension reform in a fuzzy Regression Discontinuity design. A one-hour increase in grandmothers' hours worked causes adult daughters with young children to work half an hour less. Daughters without children, with older children and sons/daughters-in-law are not affected. We show important long-run impacts on maternal labor supply and on the child penalty. Test score effects are positive for children aged 4-7 (substitution from grandparental to maternal care), and negative for children aged 11-12 (substitution from grandparental to formal childcare).
Keywords: 13; J22; J26; I38; D64; 330; spillover effects; retirement; grandparental childcare; maternal labor supply; child development